Emergency Response Measures to Alleviate a Severe Haze Pollution Event in Northern China during December 2015: Assessment of Effectiveness - Yaping Ma; Tzung-May Fu; Heng Tian; Jian Gao; Min Hu; Jianping Guo; Yangmei Zhang; Yele Sun; Lijuan Zhang; Xin Yang; Xiaofei Wang (Aerosol and Air Quality Research)
Abstract Using the WRF-Chem model, we simulated the surface PM2.5 concentrations on the North China Plain (NCP) during a severe winter haze episode (December 6–10, 2015) with the goal of assessing the effectiveness of the implemented emergency response measures (ERMs) in alleviating the pollution. We estimated that the ERMs decreased the anthropogenic pollutant emissions, with the exception of NH3, by 8–48% during this event. Inputting these reduced emission estimates, our simulations reproduced the observed PM2.5 concentrations and compositions. Stagnant regional meteorological conditions increased the lifetime of the PM2.5 in the NCP boundary layer from 1 day during the clean period to 5 days during the haze episode. Additionally, local emissions accounted for approximately only 20% of the surface PM2.5 in Beijing but more than 62% over the rest of the NCP. We found that the ERMs achieved a modest reduction in the mean surface PM2.5 concentrations during the event, decreasing them by 7% and 4% in Beijing and across the rest of the NCP, respectively. The limited effect was due to the duration of the ERMs being much shorter than the lifetime of the PM2.5, which prevented the concentrations of the latter from fully reflecting the reduction in emissions. We conclude that anthropogenic emissions on the NCP during severe winter haze episodes must be reduced by a much larger percentage to substantially abate the PM2.5 concentrations.